Pengaruh Budaya Organisasi dan Lingkungan Organisasi Terhadap Kepuasan Kerja dan Komitmen Organisasi - Dwi Junianto; Joko Sabtohadi (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
This study is aimed at investigating the effect organizational environment and organizational culture on job satisfaction and organizational commitment on PT Wahyu Daya Mandiri employes. The exploratory study to investigation to find out and explain the influence of variables aimed at testing the theory or hypothesis. The analytical tools using Smart-PLS 3.2.8 and the research method used is quantitative of path analysis. The sample in this study was taken 34 and used saturated or census sampling, which is PT Wahyu Daya Mandiri employes request to respond to the questionnaire. The results show that organizational culture, organizational climate have a positive significant impact on job satisfaction in PT Wahyu Daya Mandiri and organization culture, job satisfaction have a positive significant on organizational commitment.